The Role Of ICT In Time Planning (A Field Study At Tishreen And Tartous Universities) - باسم غدير غدير,; جميل عيسى,; حنين نوّاف عثمان , (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to identify the role of ICT in time planing at Tishreen and Tartous Universities by defining the relationship between time planning and ICT. The researcher depended on the deductive approach as a general approach for research and on the descriptive and analytical approach. She depended on simple random sampling and conducted a reconnaissance study, personal interviews and literary review. She also conducted a field study and organized, based on the literary review,a questionnaire distributing to a sample of administrative personnel from the research community. SPSS was used to download and analyze available data. This study concluded to a set of results, the most important of which is the presence of a statistically significant effect of ICT on time planning in the community under study.